If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9d + 7 + -6d = -133 Reorder the terms: 7 + -9d + -6d = -133 Combine like terms: -9d + -6d = -15d 7 + -15d = -133 Solving 7 + -15d = -133 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -15d = -133 + -7 Combine like terms: 7 + -7 = 0 0 + -15d = -133 + -7 -15d = -133 + -7 Combine like terms: -133 + -7 = -140 -15d = -140 Divide each side by '-15'. d = 9.333333333 Simplifying d = 9.333333333
| 2b^2+4b+2=0 | | 3x+2-x=6+5x-3 | | m-1/3=-9 | | 2*5x=5x*6 | | 6x+6+7x+5=115 | | 3*x=7*1x | | 6x+6+8x+7=69 | | -2=-49x(2)-7x | | 4a^2-147=0 | | -2g^2-6g+14x^2/(g+5) | | 4x+4+2x+9=31 | | -2g^2-6g+14x^2/g+5 | | 12x+16=3x+9 | | 28x^5-36x^4+8x^3= | | 7x*6=34x*6 | | 5x+2+2x+3=47 | | X/7+10=9 | | 1/2n+10=20 | | 2x-9=-33-4x | | 34x*6=7x*6 | | 2x+0.625=3x-0.625 | | X/3+5=-1 | | 3x-6=-1 | | 6x*6=7*4x | | 3x*5=7x*6 | | f(x)=4x^3+5x^2-6x-4 | | -15b^2+102b+21= | | 35=-4+5(a+3) | | 3a+2b+3c=10000 | | 4*5x=4*4x | | y-8=-4/9(18) | | 1/2(n+4)+7=12n+1/3(3n-24) |